Deformation twinning in equiaxed-grained Fe-6.5 wt.%Si alloy after rotary swaging. (15th July 2020) - Han, Chaoyu; Wen, Shibo; Ye, Feng; Wu, Wenjia; Xue, Shaowei; Liang, Yongfeng; Liu, Binbin; Lin, Junpin
Abstract: Tensile behavior of an equiaxed-grained Fe-6.5 wt.%Si alloy, which was deformed into Φ 6 mm bar by hot rotary swaging, was investigated at various temperatures (300–400 °C) and stretching rates (0.42–1 mm/min). The results revealed an enhancement in the intermediate-temperature tensile ductility after heat treatments. Deformation twinning was found in the equiaxed-grained Fe-6.5 wt.%Si bars during the tensile test, and heat treatments can enhance the deformation twinning. More twins can be observed in the necking areas than other regions. The high Schmid factor values above 0.4 after heat treatments demonstrated that deformation twinning can easily occur in the equiaxed-grained Fe-6.5 wt.%Si alloy. Higher deformation temperatures, higher strain rates, and larger degree of order suppressed the formation of deformation twinning, while the grain sizes had little effect on the deformation twinning. The twinning stress of the Fe-6.5 wt.%Si alloy increased with the increasing grain size, which did not agree with the Hall–Petch type relationship. The deformation twinning resulted in the improved ductility of the Fe-6.5 wt.%Si alloy.